Mechanistic investigations and ligand development for rhodium catalyzed [2+2+2] and zinc catalyzed [4+2] cycloadditions - Dalton, Derek M., author; Rovis, Tomislav, advisor; Wood, John L., committee member; Kennan, Alan J., committee member; Rappé, Anthony K., committee member; Snow, Christopher D., committee member (Colorado State University. Libraries, 2013)
Described herein are mechanistic studies and ligand development for Rh(I) catalyzed [2+2+2] cycloaddition reactions of alkene tethered isocyanates and exogenous alkynes. A mechanistic hypothesis has been proposed and supported through experiment. Novel perfluoroaryl Taddol phosphoramidite ligands were developed based on the mechanistic hypothesis. Improvements in product and enantioselectivity were found using the perfluoroaryl Taddol phosphoramidite ligand, CKphos. This catalyst system was studied by NMR, X-ray and DFT calculations. Rh(I)-C6F5 and Co(-1)-C6F5 interactions were found in the course of studying the CKphos catalysts. The Rh-CKphos catalyst system was used in the synthesis of the tricyclic core structure of the cylindricine and lepadiformine alkaloids. Finally a Zn(II)-catalyzed [4+2] cycloaddition of 1- azabutadienes and nitro olefins was discovered and developed as an efficient and selective means to synthesize tetrahydropyridines.
Keywords: cycloaddition; zinc; rhodium; enantioselective; heterocycles; catalysis